A comparative study between x-rays and gamma-rays irradiation on electrical characteristics of bipolar junction transistors (BJTS) - Chee, Fuei Pien; Tiwari, Anand Kumar; Alias, Afishah; Salleh, Saafie; Abdul Amir, Haider F. (American Scientific Publishers, 2017)
Irradiation impact of gamma rays and X-rays on bipolar junction transistors (BJTs) in terms of electronic excitation due to transfer of energy and subsequent ionization, as well as energy transfer to atomic nuclei is studied using in-situ method. Comparison is made on the electrical characteristics of the devices under test (DUT) for various collecting current at two different operating mode. Both temporary and permanent damages in DUTs are found to be induced by energy transfer from the irradiation by gamma-rays and X-rays, depending upon total dose absorbed and current drive. Increased probability of recombination, due to creation of electron–hole pairs at the base region is found to be the most significant radiation damage in BJTs, as it leads to decrease in electron flux reaching the collector region.